On the Resistance to Relapse to Cocaine-Seeking Following Impairment of Instrumental Cocaine Memory Reconsolidation - Exton-McGuinness, Marc T. J.; Drame, Mohamed L.; Flavell, Charlotte R.; Lee, Jonathan L. C. (Frontiers in Behavioral Neuroscience, 2019)
Reconsolidation normally functions to update and maintain memories in the long-term. However, this process can be disrupted pharmacologically to weaken memories. Exploiting such experimental amnesia to disrupt the maladaptive reward memories underpinning addiction may provide a novel therapeutic avenue to prevent relapse. Here we tested whether targeted disruption of the reconsolidation of instrumental (operant) lever pressing for cocaine resulted in protection against different forms of relapse in a rat self-administration model. We first confirmed that systemic injection of the non-competitive N-methyl–D-aspartate receptor antagonist MK-801 did impair reconsolidation to reduce spontaneous instrumental drug-seeking memory at test. This deficit was not rescued by pharmacological induction of stress with the anxiogenic α2-noradrenergic receptor antagonist yohimbine. In contrast, cocaine-seeking was restored to control levels following priming with cocaine itself, or presentation of a cocaine-associated cue. These results suggest that while stress-induced relapse can be reduced by disruption of instrumental memory reconsolidation, the apparent sparing of the pavlovian cue-drug memory permitted other routes to relapse. Therefore, future reconsolidation-based therapeutic strategies for addictive drug-seeking may need to target both instrumental and pavlovian memories.